Estimation accuracy vs. engineering significance of contact parameters for solid dampers. (4th July 2017) - Gastaldi, Chiara; Gola, Muzio M.
Abstract: All numerical models of friction-damped bladed arrays require knowledge or information of contact-friction parameters. In the literature, these parameters are typically tuned so that the experimental Frequency Response Function (FRF) of a damped blade matches its numerical counterpart. It is well known that there exist multiple combinations of contact parameters capable of satisfying a given experimental-numerical FRF match. A better approach towards a finer tuning could be based on directly measuring contact forces transmitted between blade platforms through the damper: in this case friction coefficients are estimated through tangential over normal force components during those hysteresis segments which are safely identified as being in a slip condition. This has been applied by these authors to rigid bar (solid) dampers. Unfortunately, the four contact stiffness values (left and right damper-platform contact, normal and tangential) are more than the measurements available in the technique presented by these authors. Therefore, the problem is underdetermined. The purpose of this paper is twofold, i.e., to propose an alternative way to estimate contact stiffness values ( i.e. thus solving the under-determinacy mentioned above) and to check the effective significance of such estimates from a practical engineering point of view. The contact parameter estimation technique proposed by these authors produces, for each contact parameter, a best-fit value and an uncertainty band. It will be shown that the uncertainty affecting each contact parameter results in an uncertainty on the equivalent damping and stiffness indicators at blade level which is lower than 5%.